Pain frequency moderates the relationship between pain catastrophizing and pain - Kjøgx, Heidi; Zachariae, Robert; Pfeiffer-Jensen, Mogens; Kasch, Helge; Svensson, Peter; Jensen, Troels S.; Vase, Lene (Frontiers in Psychology, 2014)
Background Pain frequency has been shown to influence sensitization, psychological distress and pain modulation. The present study examined if pain frequency moderates the relationship between pain catastrophizing and pain. Method A non-clinical (247 students) and a clinical (223 pain patients) sample completed the Danish versions of the Pain Catastrophizing Scale, Beck Depression Inventory and the State Trait Anxiety Inventory and rated pain intensity, unpleasantness and frequency Results In both samples, high pain frequency was found to moderate the association between pain catastrophizing and pain intensity, whereas low pain frequency did not. The psychometric properties and the factor structure of the Danish version of the PCS were confirmed. Conclusions This is the first study to validate the Danish version of the PCS and to show that pain frequency moderates the relationship between pain catastrophizing and reported pain in both non-clinical and clinical populations.